Effect of Fetal Sex on Maternal and Obstetric Outcomes - Al-Qaraghouli, Mohammed; Fang, Yu Ming Victor (Frontiers in Pediatrics, 2017)
Fetal sex plays an important role in modifying the course and complications related to pregnancy and may also have an impact on maternal health and well-being both during and after pregnancy. The goal of this article is to review and summarize the findings from published research on physiologic and pathologic changes that may be affected by fetal sex and the effect of these changes on the maternal and obstetrical outcomes. This will help create awareness that fetal sex is not just a random chance event but an interactive process between the mother, the placenta and the fetus. The reported effects of male sex on the course of pregnancy and delivery include: higher incidence of preterm labor in singletons and twins, failure of progression in labor, true umbilical cord knots, cord prolapse, nuchal cord, higher cesarean section rate, higher heart rate variability with increased frequency and duration of decelerations without acidemia and increased risk of gestational diabetes mellitus (GDM) through the poor beta cells function. Similarly, female fetal sex has been reported to modify pregnancy and delivery outcomes including: altered fetal cardiac hemodynamics, increased hypertensive diseases of pregnancy, higher vulnerability of developing type 2 DM after pregnancy possibly because of influences on increased maternal insulin resistance. Placental function is also influenced by fetal sex. Vitamin D metabolism in the placenta varies by fetal sex; and the placenta of a female fetus is more responsive to the relaxing action of magnesium sulfate. Male and female feto-placental units also vary in their responses to environmental toxin exposure. The association of fetal sex with stillbirths is controversial with many studies reporting higher risk of stillbirth in male fetuses; although some smaller and limited studies have reported more stillbirths with female fetus pregnancies. Maternal status such as BMI may in turn also affect the fetus and the placenta in a sex specific manner. There is probably a sex specific maternal-placental-fetal interaction that has significant biological implications of which the mechanisms may be genetic, epigenetic or hormonal. Determination of fetal sex may therefore be an important consideration in management of pregnancy and childbirth.